College physics - Serway, Raymond A.; Vuille, Chris; Hughes, John (Cengage Learning, 2018)
Comprised of the first 14 chapters of Serway/Vuille's proven textbook. This book helps students master physical concepts, improve their problem-solving skills, and enrich their understanding of the world around them. The authors provide a consistent problem-solving strategy and an unparalleled array of worked examples to help students develop a true understanding of physics